Noise reduction and cost saving analysis for pneumatic and electrical system of microgrinder at CNC area - Nur Atiqah, Alias (2018)
are over and insufficient stripping because of the air micro grinder that need frequently maintenance. Changes of system from pneumatic and electrical system is the main solution to this problem. After the changes, electrical system shows the lowest noise contribution to the surrounding and the changes help from 161% to 244% noise reduction. The permissible exposure limits (PELs) of noise based on Occupational Safety and Health (OSHA) criterion can also be meet when the changes of system occur. In addition, the benefits from the changes of the system is USD 273.26 with only 3 month of payback period and 97% return of investment (ROI). This high ROI means the investment’s gain compare favorably to its cost. Based on total saving in term of labour cost, the total downtime of the machine is decreasing causing increasing of the effective hour and directly proportionally increase in total saving of labour cost. Indirectly when the system changes, the machine downtime is minimized that provide maximized efficiency, increases machine availability which in turn increase through output and minimized reject that also reduces order lead times and increase customer satisfaction. At the same time, ergonomic in occupational safety and health can be achieved when the noise exposure follows the OSHA criterion and it’s also help increases the total saving in two main categories for the company itself which is in term of part and labour.